Studying of the hydrocarbon-oxidizing potential of the Caspian region bacteria associations for creation of preparations for bioremediation (Experimental biology, 2018)
At the present stage of development of the oil-producing and oil-refining industries in Kazakhstan, it is not possible to completely exclude environmental pollution by oil and oil products, which makes it urgent to carry out works aimed to solving this environmental problem. As an effective means of the environment protecting, the biological method of purification has proved itself. Increasingly bioremediation uses aboriginal microorganisms from specific pollution sites, as these cultures are adapted to the prevailing climatic and ecological conditions, which gives a number of advantages to the consortia formed on their basis.In this work the hydrocarbon-oxidizing potential of native bacteria from Caspian region in Kazakhstan and its associations was studied and the most effective consortia were selected to create preparations for bioremediation.12 strains of bacteria isolated from water and soil samples collected in the Karazhanbas and Kalamkas fields were demonstrated stable and intensive growth on the medium with oil. In these cultures several characteristics such as oil degradation percentage, emulsification index, cell surface hydrophobicity and antagonistic activity were studied. On the basis of these strains bacterial associations were compiled. The growth potential and hydrocarbon-oxidizing activity under laboratory model experiments were investigated in these associations. The consortia with the greatest degradation capacity were selected: Achromobacter denitrificans skar13 + Rhodococcus fascians skar21, Roseomonas mucosa wkal24 + Stenotrophomonas chelatiphaga wkal49 and Ochrobactrum sp.wkal48 + Sphingobacterium kitahiroshimense wkar54. The association of Achromobacter denitrificans skar13 + Rhodococcus fascians skar21 degraded 73.1 ± 6.9% of oil hydrocarbons, 94.6 ± 8.6% of diesel fuel hydrocarbons, 79.7 ± 6.2% of gasoline hydrocarbons. Complex of Roseomonas mucosa wkal24 + Stenotrophomonas chelatiphaga wkal49 destroyed 96.8 ± 5.7% of oil fractions, 97.8 ± 7.9% of diesel fractions and 86.2 ± 7.3% of gasoline fractions. The consortium of Ochrobactrum sp.wkal48 + Sphingobacterium kitahiroshimense wkar54 reduced the content of petroleum hydrocarbons on 83.5 ± 7.2%, diesel on 88.7 ± 8 and gasoline on 74.3 ± 6.9%.These bacterial associations are promising as bio destructors of hydrocarbons and can be used in bioremediation of environmental pollution.
Keywords: bioremediation; bacterial associations